2017
DOI: 10.1111/jcal.12190
|View full text |Cite
|
Sign up to set email alerts
|

Medical students' attitudes towards the use of virtual patients

Abstract: An increasing number of virtual patients (VPs) are being used in the classroom, which raises questions about how to implement VPs to improve students' satisfaction and enhance their learning. This study developed and validated a scale that measures acceptability and attitudes of medical students towards the use of the VP education tool in the classroom. This mixed method study first explored attitudes with 11 students in two focus groups. Later on, eight experts performed item reduction and transformation thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Simulation-based learning (SBL) continues to increase in popularity in medical education, ranging from simulations of resuscitation scenarios for medical students on their first day, to resident physicians practicing central venous catheters, to multi-disciplinary teams practicing communication during primary and secondary assessments of trauma patients [1][2][3]. Prior studies have shown that exposure to SBL, even in undergraduate education, can increase clinical success specifically regarding technical skills such as CPR and airway management [4].…”
Section: Introductionmentioning
confidence: 99%
“…Simulation-based learning (SBL) continues to increase in popularity in medical education, ranging from simulations of resuscitation scenarios for medical students on their first day, to resident physicians practicing central venous catheters, to multi-disciplinary teams practicing communication during primary and secondary assessments of trauma patients [1][2][3]. Prior studies have shown that exposure to SBL, even in undergraduate education, can increase clinical success specifically regarding technical skills such as CPR and airway management [4].…”
Section: Introductionmentioning
confidence: 99%
“…Medical and healthcare education is media- and resource-dependent in nature. It has become increasingly prevalent to integrate technology-enhanced learning (TEL) resources and promote the reform of information technology (IT)-based teaching models in higher medical and healthcare education [ 14 ]. The most representative example in the field is simulation-based medical and healthcare education, especially high-fidelity simulation, which can bridge the gap between theory and practice by immersing learners in a realistic setting [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medical education is media-relevant and resource-dependent in nature. It has become increasingly prevalent to integrate Technology Enhanced Learning (TEL) resources and promote the reform of information technology (IT)-based teaching models in higher medical education [14]. The most representative example in the eld is simulation-based medical education, especially the high-delity simulation which can bridge the gap between theory and practice by immersing the learner in the realistic setting [15].…”
Section: Introductionmentioning
confidence: 99%